Uso de ambientes virtuais de aprendizagem nos cursos técnicos sob o olhar de professores - Schmidt, Maria Cristina Cezimbra (2017)
This research was developed in the Post-Graduate Program in Professional and Technological Education of the Industrial Technical College of Santa Maria (PPGEPT - CTISM), Academic Master, in the line of research in Innovation for Professional and Technological Education. The general objective of this study was to study the use of virtual environments for teaching and learning (VLE) in Technical Education at the Middle Level, it is necessary to identify this digital culture in the classroom everyday, since it is known that Professional Education Work and most companies use technologies in their daily lives, so they look for people who can interact with them, as digital technologies transform schools into more attractive spaces, connect training with the need of social life and prepare Students for the professional activity of the future. The authors who guided this research Coll (2010), Kenski (2012, 2013) Moran (2013), Rosini (2007) among others, and for the development of this research was made a case study, with qualitative and quantitative analysis, , Among other data, the lack of knowledge of teachers for the use of the resources of the virtual environment MOODLE, its impacts on teaching and student participation. This research shows that while having access to the technologies, many teachers 'classroom practice is still far from the students' everyday life, and also the need to use virtual teaching environments, and this can be a complication in training for the work. As future work, this research suggests training projects, in a modular way, for the community involved.